Production of polymeric nanofibers with different conditions of the electrospinning process - Vaz,Bruna da Silva (2017)
ABSTRACT Nanofibers are materials that present high elasticity, strength, porosity and surface-area-to-volume ratio. The electrospinning method is the most widely adopted technique for forming polymeric nanofibers due to repeatability, easy scale-up process and production of long and continuous nanofibers. This method produces nanofibers with diameters ranging from 10 nm to 1000 nm. The process is regulated by many parameters which significantly affecting the morphology of the nanofibers, and through the proper handling of these parameters are obtained desired nanofibers in morphology and diameters. Based on this, the objective of this work was to evaluate the size and morphology of nanofibers obtained by different conditions of the electrospinning process. The electrospinning technique will be utilized to produce nanofibers with polyacrylonitrile (PAN) polymer and solvent N, N-dimethylformamide (DMF). The polymer solutions (10% (w/v)) were injected through of the capillary with diameter 0.45; 0.55; 0.70 and 0.80 mm. The distances from the collector to the capillary were tested between 100 and 200 mm, voltage between 15 and 25 kV, and feed rate of the solution between 100 and 1000 µL/h. All of the tests were conducted at 22 °C with the relative humidity level controlled at 65±1%. The morphology and size of nanofibers were evaluated by Scanning Electron Microscopy (SEM). Thus, the development of nanofibers with small diameter and high pore volume facilitate bioactive molecules loading and / or transport of nutrients and wastes, and allow the polymeric nanofibers become important class of biomaterials.